دور المشكلات النفسية والاجتماعية على الذكاء الانفعالي عند طلبة جماعة الثقافة الإسلامية بجامعة السلطان قابوس - أحمد بن عزان بن سيف البحري
The aim of the research is to study the relationship of psychological and social conditions to emotional intelligence among students of Islamic culture at Sultan Qaboos University in the Sultanate of Oman. Where the researcher relied on the descriptive approach. The study population consisted of Sultan Qaboos University students. As for the study sample, it consisted of 242 male and female students who were selected by following the stratified random method. The result of the exploratory study showed that the scale was of high quality, as the value of the reliability coefficient reached 0.854 and indicated the validity of the scale and its suitability for conducting scientific research. The researcher used a set of statistical methods represented in exploratory factor analysis, multiple linear regression to analyze the potential relationships between the studied variables, and multiple analysis of variance for the dependent variables. The results showed that there were no strong correlations between the studied dimensions, as the strongest relationship between the axis of self-confidence and the axis of emotional awareness reached (0.259). The weaker the relationship was, the more influential it was among the other variables. The results showed the absence of strong correlations between the dimensions of each of the psychological and social problems and the dimension of emotional regulation, where the strength of the correlations ranged between (0.057-0.236). The results showed with regard to the correlation coefficients between the dimensions of psychological and social problems (independent) and the empathy dimension for the emotional intelligence variable (dependent), where the strength of the correlations ranged between (0.051-0.236), and this result indicates that the weakest relationship occurred between the empathy dimension and each of the two dimensions of stress. Psychological and depression. As for the correlation coefficients between the dimensions of psychological and social problems and the social communication dimension of the emotional intelligence variable, the results indicated that the strongest relationship came between the social communication dimension and the social adjustment dimension, although it is the strongest relationship, but it did not come out of being a weak relationship (0.315). The results showed with regard to the correlation coefficients between the dimensions of psychological and social problems, and after self-motivation for the emotional intelligence variable, where the strength of the correlations ranged between (0.057-0.250), and this result indicates that the weakest relationship occurred between the dimension of depression and self-confidence, and the strongest relationship was between the dimension of depression and self-confidence, and the strongest relationship was between the Self-motivation on the one hand and social adjustment on the other. The researcher recommended considering the dimensions of emotional intelligence when enacting laws, educational systems and student activities among students of Sultan Qaboos University. Preparing various courses, lectures and seminars in developing the emotional intelligence of university students. He also recommended conducting a study entitled: "The role of the family in solving psychological and social problems through the techniques of emotional intelligence, the Omani family as a model", and conducting a study linking Islamic principles and techniques of emotional intelligence among students of Sultan Qaboos University.